Gay suburban narratives in American and British culture : homecoming queens - Dines, Martin, 1976- (Palgrave Macmillan, 2010)
"Martin Dines explores the relationship between the physical and metaphorical spaces of suburbia and the evolution of modern gay identities across a range of British and American film and fiction, looking at the work of Dennis Cooper, Quentin Crisp, Todd Haynes, Christopher Isherwood, Kevin Killian, David Leavitt, Oscar Moore and Edmund White"--Resumé vydavatele
Keywords: homosexualita a literatura; gayové; homosexualita a společnost -- Spojené státy americké; homosexualita a společnost -- Velká Británie; anglická literatura; americká literatura; homosexuality and literature; gay men; homosexuality and society -- United States; homosexuality and society -- Great Britain; English literature; American literature; studie; studies